Joint analysis of environmental and risk policies: Methodology and application to the French case. Issue 101 (November 2019) - Vigier, E.; Curt, C.; Curt, T.; Arnaud, A.; Dubois, J.
Highlights: We provide a method for analyzing the French law on natural hazards and environmental protection for land planning. A diagnosis of the coherence and difficulties related to the implementation of public policies at the local level is presented. We present an inventory of regulatory texts. An analytical model for identifying and linking risk management tools is presented. We present its application to 3 French territories. Abstract: French public authorities have to manage the protection of the environment and risks. This study proposes a method for analyzing the French law on environmental hazards and the protection of the environment in the context of land planning. The main question asked is: Do the difficulties of implementing environmental policies stem from the complexity of the law or from the organization of local land management? The final aim is to offer reading keys to aid local planning decisions in France. The approach proposed is based on collecting and organizing the regulations, analyzing their application in practice, and comparing the legal standpoints to the logic of local decision-makers. This study demonstrates the extent to which French environmental regulations are complex and how they can be adapted locally in order to improve their application and efficiency.